Pengaruh Bermain Game Online Terhadap Minat Belajar Peserta Didik Dalam Pembelajaran Pendidikan Agama Islam - Arif Syahputra Sinaga; Wirdati Wirdati (An-Nuha, 2022)
This study aims to determine the effect of playing online games on students' learning interest in learning Islamic Religious Education at SMP Negeri 25 Padang. This research is associative quantitative research. The population in this study were students of class IX SMP Negeri 25 Padang. The sample used was 72 people, the sampling technique was cluster random sampling. The data analysis technique uses the t-test, so normality and linearity tests are needed. Based on the analysis of the research results, it can be concluded that: playing online games has a significant effect on interest in learning with t count -5.189 > t table -1.666, with a significant level of 0.05. The significant value of motivation is 0.000 and the value is smaller than the probability of 0.05 (0.000 <0.05). It can be concluded that Ha = accepted, which means that there is a significant influence between playing online games on interest in learning at SMP Negeri 25 Padang.